AHMAD DAHLAN DAN PESANTREN: GERAKAN PEMBAHARUAN PENDIDIKAN, DAKWAH, DAN PEMBERDAYAAN MASYARAKAT DI INDONESIA - Anwar Nuris (Institut Dirosat Islamiyah Al-Amien Prenduan Sumenep, 2016)
Islamic revitalization movement in Indonesia could not be separated from the figure of Ahmad Dahlan as a founder of Muhammadiyah. This can be traced through the early history and development of Muhammadiyah which is indicated by the lights of Ahmad Dahlan through Islamic revitalization movement. This article observes the personage of KH. Ahmad Dahlan from anthropological and sociological view. This observation is intended to find out the role of the person in the map of community development. The main aim of this article investigates correlation between the figure of KH. Ahmad Dahlan and educational system of the Islamic boarding school (pesantren) in Indonesia. The correlation of Muhammadiyah and Islamic boarding school is examined thorugh three categories as significant indicators to show the function and role of the Muhammadiyah. The three categories are: educational institution and the development of Islamic teachings, institution of struggle and Dakwah Islamiyah, and institution for community empowerment and public service. Of the three categories, this study found that KH. Ahmad Dahlan is a figure who could respond to its latest challenges quickly and precisely through revitalization movement in the field of education, dakwah, and community empowerment in Indonesia.